(untitled) (Revista de Ciências Agroveterinárias, 2024)
This review elucidated the main effects of in ovo nutrition with fatty acids and their relationship with the immune system of producing birds. We searched the main research databases Web of Science and Google Scholar for articles published in the last 20 years, and found 75 files that reported this approach. Ovo nutrition is a technique used in poultry farming, and its efficiency in nutritional management, which combines preventive and health management, has been discussed. This technique’s main objective is to provide nutrients even in the embryonic phase of the animal, instigating the functioning of specific intestinal cells, resulting in benefits that can be reflected after birth, as recommended by immune nutrition, in the case of nutrient supplementation that stimulates defense cells of the organism. In the pursuit of precision animal husbandry, advanced and easily applicable techniques are being increasingly explored. Specific nutrients, such as essential fatty acids, enhance the gastrointestinal microbiota, maintain intestinal integrity, and act as necessary substrates to ensure a satisfactory immune response in poultry. This has proven to be highly beneficial for animal production. Studies have demonstrated that the use of these nutrients can effectively improve poultry production in a sustainable and economically viable manner. In conclusion, incorporating essential fatty acids into poultry feed represents a promising and practical strategy within precision animal husbandry. In addition to promoting gut and immune health in birds, this practice contributes to more efficient, sustainable, and economically advantageous production, which aligns with current demands in the poultry industry.